Strategi Seleksi dan Recording Sederhana pada Kambing Lokal di Kelompok Ternak Sumber Tani Baru Kecamatan Poasia Kota Kendari: Simple Selection and Recording Strategies for Local Goats in the Sumber Tani Baru Farmer Group, Poasia District, Kendari City - Badaruddin, Rusli; Prasanjaya, Putu Nara Kusuma; Pagala, Muhammad Amrullah; Rusdin, Muh; Aka, Rahim; Rahadi, Syam; Hakim, Muh Haidir (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2026)
This community service activity aimed to improve farmers’ knowledge and skills in implementing selection strategies and simple recording systems for local goats to support increased livestock productivity. The activity was conducted at the Sumber Tani Baru Livestock Farmer Group, Poasia District, Kendari City, targeting local goat farmers. The method used was a participatory approach, including observation, counseling, training, demonstrations, and mentoring. The results showed an improvement in farmers’ knowledge and skills in selecting superior does and bucks, as well as in recording livestock data. Farmers were able to identify superior animals based on specific criteria and began to implement simple recording systems to monitor livestock performance. In addition, farmer participation was relatively high, as indicated by active involvement in discussions and field practices. This activity proved effective in enhancing farmers’ capacity and has the potential to support sustainable improvement in local goat productivity.